2002
DOI: 10.1021/bi016059f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution Viscosity on Intramolecular Electron Transfer in Sulfite Oxidase

Abstract: Our previous studies have shown that the rate constant for intramolecular electron transfer (IET) between the heme and molybdenum centers of chicken liver sulfite oxidase varies from approximately 20 to 1400 s(-1) depending upon reaction conditions [Pacheco, A., Hazzard, J. T., Tollin, G., and Enemark, J. H. (1999) J. Biol. Inorg. Chem. 4, 390-401]. These two centers are linked by a flexible polypeptide loop, suggesting that conformational changes, which alter the Mo-Fe distance, may play an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
172
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(189 citation statements)
references
References 46 publications
(54 reference statements)
15
172
1
Order By: Relevance
“…Recent studies of mammalian SOX kinetics showed that the IET rate was impacted by solution viscosity (13,14), confirming the hypothesis that the Cyt b domain was undergoing a large conformational change during catalysis relative to the Mo-MPT-containing sulfite-oxidizing module (9). NaR has a similar structure to SOX in that the Cyt b domain is tethered to the Mo-MPT-containing nitrate-reducing module via a flexible "hinge" sequence.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…Recent studies of mammalian SOX kinetics showed that the IET rate was impacted by solution viscosity (13,14), confirming the hypothesis that the Cyt b domain was undergoing a large conformational change during catalysis relative to the Mo-MPT-containing sulfite-oxidizing module (9). NaR has a similar structure to SOX in that the Cyt b domain is tethered to the Mo-MPT-containing nitrate-reducing module via a flexible "hinge" sequence.…”
mentioning
confidence: 65%
“…The k cat values were calculated based on the Mo-MPT content when available or normalized to known values (1,2,11,12). No K m determinations were done, because it has been shown that this parameter was independent of the viscosity for some enzymes (14,17) and it was assumed that all of the forms would be impacted to the same degree.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations